Response Analysis of Training Participants in Making Digital Teaching Materials According to the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum at IAIN Curup - Medriati, Rosane; Risdianto, Eko; Bahri, Syaiful; Siswanto, Siswanto (Asosiasi Profesi Multimedia Indonesia, 2022)
The purpose of this study was to analyze the responses of the training participants in making digital teaching materials according to the Merdeka Belajar Kampus Merdeka (MBKM) curriculum at IAIN Curup.This activity was carried out in July 2022 at the Institut Agama Islam Negeri (IAIN Curup). The target audience for this service activity is the education community, namely IAIN Curup. The target of this service is lecturers at IAIN Curup. However, the research sample was only 25 lecturers who were participants in the training held by the service team from Bengkulu University. Data was collected by means of surveys in the form of response questionnaires distributed to lecturers who were trainees whose purpose was to measure the success of this activity process. These results were then analyzed quantitatively and descriptively. The questionnaire used as a data collection tool in this activity was developed by following a modified Likert Scale with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree. The results of this study shows that the training has been carried out well, both in terms of the material, the method of delivery, the software used, how to guide practical activities and the compatibility between digital teaching materials made with the characteristics that teaching materials must possess. In addition, this training activity is also able to motivate or encourage training participants to create and provide digital teaching materials that arein accordance with the Merdeka Belajar Kampus Merdeka (MBKM) by considering the needs of students, campuses, and regions, and encouraging them to be more creative in innovating teaching materials.